Protective effect of Yunkang oral liquid via regulating androgen receptor in polycystic ovary syndrome rats - Xiang Zheng; Chuanjie Zhou; Wanfeng Xu; Jiujie Jia; Bo Li; Guiyuan Lv; Suhong Chen (Gynecological Endocrinology)
Objectives: This study aimed to explore the effect and mechanism of Yunkang oral liquid (YK) on polycystic ovary syndrome (PCOS). Methods: PCOS model rats were prepared by injecting exogenous androgen dehydroepiandrosterone, and YK was administered simultaneously for 28 days during modeling. The morphology of ovaries and uterus was observed using H&E staining, and serum levels of testosterone (T), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) were determined by radioimmunoassay. Additionally, serum lipids (TG, HDL-c), blood glucose (GLU), and aminotransferase (AST, ALT) levels were detected. The expression of androgen receptor (AR) protein was determined by Western blotting. Results: YK treatment resulted in reduced serum levels of T, LH and FSH, ameliorated ovarian polycystic-like pathological changes and uterine morphology in PCOS rats, and decreased serum TG, GLU, AST and ALT levels, elevated serum HDL-c levels, and improved abnormalities of glycolipid metabolism accompanying PCOS. Moreover, YK decreased the expression of ovarian AR in PCOS rats. Conclusions: This study indicates that YK may protect the ovaries by inhibiting the expression of AR, which could be a potential treatment for PCOS.